Motivational factors affecting sports consumption behaviours of S-league spectators - Teo, Yu Run (2018)
The decline in S-League spectatorship in recent years is a concern for the local sporting scene and the cause of this is multi-factorial. This study looks into the profile of the spectators and aims to examine the relationship between eight motivational factors and the sports consumption behaviour of S-League spectators. This study utilized a survey questionnaire adapted from the study by Kuo and Tay (2009) as the main instrument for data collection. 185 participants were recruited with the pre-requisite to have watched at least one S-League game in the 2017 season. Multiple regression analyses were carried out and it was found that these eight motivational factors significantly, but not sufficiently explained the variances. Only four of the motivational factors were found to be of statistical significance. Entertainment was found to be the strongest predictor explaining the variance of the 2017 season attendance frequency; followed by Social Interaction and Escape. Similarly, Entertainment was found to be the strongest predictor explaining the variance of the 2018 season intended attendance frequency; followed by Social Interaction, Escape and Economic. The result suggests that relevant authorities can focus on different aspects of the game such as the entertainment value, promoting social interaction among the spectators to improve the attendance of the league. This study will provide valuable insights for the S-League and football clubs to better understand the profile of the spectators and allow them to evaluate their current marketing strategies in attracting more spectators in the future.